A new method for the treatment of ligneous conjunctivitis - Fırat, Tanju (The Turkish Journal of Pediatrics, 1969)
Two cases of ligneous conjunctivitis observed at the Department of Ophthalmology, Hacettepe University, are reported, the second of which was treated by local application of hyaluronidase combined with alpha chymotrypsine. This case was, presumably, the third one in the world to be treated by this method, and is a typical example of the satisfactory treatment of the disease for which all previous attempts were unsuccessful.